2018
DOI: 10.32674/jis.v8i2.120
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Cross-Cultural Competence and Social Support on International Students’ Psychological Adjustment: Autonomy and Environmental Mastery

Abstract: This study investigated relationships between cross-cultural competence, social support, and international students’ psychological adjustment. Participants included 94 international students studying in the United States. The researchers conducted a series of standard multiple regression analysis to predict autonomy and environmental mastery as measured by the Ryff Scales of Psychological Well-Being (Ryff & Keyes, 1995). They found significant positive relationships between autonomy and cross-cultural comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…For international students, social support is a fundamental resource by which they cope with acculturative stress and its consequences, such as depression, anxiety, and somatic symptoms (Jou & Fukada, 1997;Lee et al, 2004;Ra & Trusty, 2017;Zhang & Goodson, 2011). Some studies (Aldawsari et al, 2018;Berger et al, 2018;Brisset et al, 2010;O'Reilly et al, 2010) have considered well-being the result of the positive effect of social support on loneliness (Lin & Kingminghae, 2014) or stress (O'Reilly et al, 2015). Other studies exploited international students' life satisfaction in relation to functional support (Yusoff, 2012) or to their need for support, information, and feedback (Bektaş et al, 2009).…”
Section: Social Support and International Studentsmentioning
confidence: 99%
“…For international students, social support is a fundamental resource by which they cope with acculturative stress and its consequences, such as depression, anxiety, and somatic symptoms (Jou & Fukada, 1997;Lee et al, 2004;Ra & Trusty, 2017;Zhang & Goodson, 2011). Some studies (Aldawsari et al, 2018;Berger et al, 2018;Brisset et al, 2010;O'Reilly et al, 2010) have considered well-being the result of the positive effect of social support on loneliness (Lin & Kingminghae, 2014) or stress (O'Reilly et al, 2015). Other studies exploited international students' life satisfaction in relation to functional support (Yusoff, 2012) or to their need for support, information, and feedback (Bektaş et al, 2009).…”
Section: Social Support and International Studentsmentioning
confidence: 99%
“…Caligiuri et al (1998) applied the spillover theory to the cross-cultural context when examining whether family support, family communication, and family adaptability are significantly related to expatriate adjustment. For international students as SIEs, the work domain (e.g., class tasks, study, and/or research) and the personal domain are interrelated; in other words, international students cannot succeed in one while failing in the other; thus, support from personal entities (e.g., family and the community) is crucial for their adjustment and academic success (e.g., Aldawsari et al, 2018;Martirosyan et al, 2019).…”
Section: Spillover Theorymentioning
confidence: 99%
“…In the international higher education literature, results about the influence of family support on international students' outcomes in HEIs are inconsistent. Aldawsari et al (2018) studied 94 international students in the United States and found that social support from family and friends significantly affected international students' psychological adjustment. Bulgan and Çiftçi (2018), however, found a nonsignificant relationship between social support and psychological adjustment based on their study with 243 married international graduate students in the United States.…”
Section: Perceived Family Supportmentioning
confidence: 99%
“…They explained that when international students feel supported socially and academically, they have a higher sense of belonging, which in turn leads to success. Further, when international students appreciate the support around them, they are more likely to feel that they have mastered their environment and surpassed the stressors that might have inhibited their success earlier in their arrival (Aldawsari et al, 2018). These findings challenge researchers and student affairs professionals to better understand the contours and complexities of supporting international students (Briggs & Ammigan, 2017;Madden-Dent et al, 2019).…”
Section: Supportmentioning
confidence: 99%